2014
DOI: 10.1098/rsos.140193
|View full text |Cite
|
Sign up to set email alerts
|

Conidia of the insect pathogenic fungus, Metarhizium anisopliae , fail to adhere to mosquito larval cuticle

Abstract: Adhesion of conidia of the insect pathogenic fungus, Metarhizium anisopliae, to the arthropod host cuticle initially involves hydrophobic forces followed by consolidation facilitated by the action of extracellular enzymes and secretion of mucilage. Gene expression analysis and atomic force microscopy were used to directly quantify recognition and adhesion between single conidia of M. anisopliae and the cuticle of the aquatic larval stage of Aedes aegypti and a representative terrestrial host, Tenebrio molitor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 49 publications
(53 reference statements)
1
28
0
3
Order By: Relevance
“…In this study, Culex larvae infected with blastospores produced higher levels of phenoloxidase than that observed during infection with conidia and PO was detected one hour earlier in larvae infected with blastospores when compared to larvae infected with conidia and much earlier than that reported for Ae. aegypti larvae [14]. These observations show that not only is the Culex immune response different from that of Aedes but PO plays a more important role in the former, which is supported by the fact that melanisation at infection sites and of circulating blastospores was only observed in Culex larvae.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, Culex larvae infected with blastospores produced higher levels of phenoloxidase than that observed during infection with conidia and PO was detected one hour earlier in larvae infected with blastospores when compared to larvae infected with conidia and much earlier than that reported for Ae. aegypti larvae [14]. These observations show that not only is the Culex immune response different from that of Aedes but PO plays a more important role in the former, which is supported by the fact that melanisation at infection sites and of circulating blastospores was only observed in Culex larvae.…”
Section: Discussionmentioning
confidence: 93%
“…aegypti larvae through multiple penetration sites with blastospores readily adhering and penetrating the insect cuticle as well as penetrating the gut epithelium following ingestion by the larvae [12]. In contrast, conidia of the same fungus fail to adhere to the larval cuticle but cause death through protease-induced stress following ingestion [13,14]. There were, however, clear differences in the susceptibility of Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage of the fungal infection process is spore adhesion to the surface of the arthropod's body. In this stage, two types of proteins are produced: hydrophobins (whose layers disintegrate during the sporulation of spores) and adhesins (MAD1 and MAD2), which enable both close adhesion to the insect's cuticle and recognition of the host by the fungal pathogen (Wang and Leger 2007;Greenfield et al 2014).…”
Section: Adhesinsmentioning
confidence: 99%
“…The mode of action of EPF involves conidial attachment to the host surface followed by germination and penetration of the host cuticle through a combination of enzymatic activity and mechanical force (Arruda, Lübeck, Schrank, & Vainstein, 2005;Inglis et al, 2012;Quintela & McCoy, 1998). However, some insects have evolved a number of mechanisms to keep pathogens at bay that include (a) production of cuticular antimicrobial lipids, proteins and metabolites (Greenfield, Lord, Dudley, & Butt, 2014;Pedrini et al, 2015); (b) shedding of the cuticle during development; (c) behavioural-environmental adaptations such as induced fever, burrowing and grooming (Oi & Pereira, 1993;Siebeneicher, Bradleigh, & Kenerley, 1992).The low pathogenicity of the selected EPF isolates to S. recurvalis larvae could be due to cuticular or behavioural environmental adaptations that warrant further research to elucidate the exact reasons for this low pathogenicity reported in the present study.…”
Section: Interactions Between Metarhizium Anisopliae Isolate Icipe mentioning
confidence: 99%